New weapons to fight a new enemy: A systematic review of drug combinations against the drug‐resistant fungus Candida auris. Issue 11 (3rd April 2021) - Aghaei Gharehbolagh, Sanaz; Izadi, Alireza; Talebi, Meysam; Sadeghi, Fatemeh; Zarrinnia, Ali; Zarei, Fateme; Darmiani, Kimia; Borman, Andrew M.; Mahmoudi, Shahram
Abstract: Candida auris is an emerging and drug‐resistant pathogen. Drug combination is a promising approach against such pathogens. This study was conducted to provide an overview of all the studied drug combinations against C. auris . Relevant articles reporting results of any drug/non‐drug combinations against C. auris were found by a systematic search in PubMed, Scopus and Web of Science (ISI), and in Google Scholar up to 1 October 2020. From 187 articles retrieved in the primary search, 23 met the inclusion criteria. In total, 124 different combinations including antifungal with antifungal (45), antifungal with other antimicrobials (11), antifungal with non‐antimicrobials (32), antifungal with natural compounds (25) and between natural compounds (11) have been reported. Complete or partial synergistic effects have been reported for 3 out of 45 (6.67%) combinations of two antifungal agents, 8 out of 11 (72.73%) combinations involving antifungal agents and antimicrobials, 15 out of 32 (46.88%) of combinations between antifungal agents with non‐antimicrobials, 16 out of 25 (64%) of combinations involving antifungal agents and natural compounds, and 3 out of 11 (22.27%) of combinations involving multiple natural compounds. Antagonistic interactions have been reported for 1 out of 32 (3.13%) and 8 out of 25 (32%) of combinations between antifungal drugs with non‐antimicrobials and with natural compounds, respectively. Different drugs/compounds could potentiate the activity of antifungal drugs using this approach. However, despite the availability of this promising initial data, many more studies will be required to elucidate whether favourable interactions observed in vitro might translate into tangible clinical benefits.